Meaning in Life as a Moderator of the Association Between Future Anxiety and Depression - Adhitama, Farrell; Geshica, Lavenda (Faculty of Psychology, Universitas Gadjah Mada, 2026)
This study examines meaning in life as a moderator of the association between future anxiety and depression in 251 final-year university students in Yogyakarta, Indonesia (aged 18-25). Finishing university, a key time in young adulthood, can be stressful and increase the risk of future anxiety and depression. We investigated whether meaning in meaning-in-life dimensions (Presence and Search) moderate this relationship. Participants selected through a purposive sampling process completed the Dark Future Scale, the PHQ-9, and the Meaning in Life Questionnaire. Moderated Regression Analysis revealed that future anxiety predicts depression (β = -0.570, p < .05). While having a sense of meaning did not change the relationship, actively searching for meaning weakened the connection between future anxiety and depression. These findings suggest a complex role for meaning in life, as actively searching for meaning may strengthen the impact of future anxiety on depression. It is important for support programs to consider how different aspects of finding meaning affect students’ mental health.